Chemoreflex sensitization occurs in both male and female rats during recovery from acute lung injury - Kamra, Kajal; Zucker, Irving H.; Schultz, Harold D.; Wang, Han-Jun (Frontiers in Physiology, 2024)
Introduction-Sex-specific patterns in respiratory conditions, such as asthma, COPD, cystic fibrosis, obstructive sleep apnea, and idiopathic pulmonary fibrosis, have been previously documented. Animal models of acute lung injury (ALI) have offered insights into sex differences, with male mice exhibiting distinct lung edema and vascular leakage compared to female mice. Our lab has provided evidence that the chemoreflex is sensitized in male rats during the recovery from bleomycin-induced ALI, but whether sex-based chemoreflex changes occur post-ALI is not known. To bridge this gap, the current study employed the bleomycin-induced ALI animal model to investigate sex-based differences in chemoreflex activation during the recovery from ALI.Methods-ALI was induced using a single intra-tracheal instillation of bleomycin (bleo, 2.5 mg/Kg) (day 1). Resting respiratory frequency (fR) was measured at 1-2 days pre-bleo, day 7 (D7) post-bleo, and 1 month (1 mth) post-bleo. The chemoreflex responses to hypoxia (10% O2, 0% CO2) and normoxic-hypercapnia (21% O2, 5% CO2) were measured before bleo administration (pre-bleo) and 1 mth post-bleo using whole-body plethysmography. The apnea-hypopnea Index (AHI), post-sigh apneas, and sighs were measured at each time point.Results-There were no significant differences in resting fR between male and female rats at the pre-bleo time point or in the increase in resting fR at D7 post-bleo. At 1 mth post-bleo, the resting fR was partially restored in both sexes but the recovery towards normal ranges of resting fR was significantly lower in male rats. The AHI, post-sigh apneas, and sighs were not different between male and female rats pre-bleo and 1 mth post-bleo. However, at D7 post-bleo, the male rats exhibited a higher AHI than female rats. Both male and female rats exhibited a sensitized chemoreflex in response to hypoxia and normoxic-hypercapnia with no significant differences between sexes.Conclusions-A sex difference in resting ventilatory parameters occurs post ALI with a prolonged increase in resting fR and larger AHI in male rats. On the other hand, we did not find any sex differences in the chemoreflex sensitization that occurs at 1 mth post-bleo. This work contributes to a better understanding of sex-based variations in lung disorders.